Why skaldic verse? Fashion and cultural politics in thirteenth-century Iceland - Nordal, Guðrún (Universität Tübingen, 2004)
Skaldic verse became one of the class symbols of the Icelandic aristocracy of the thirteenth century. Abroad the more influential chieftains possible gained access to royal courts through their verse-making, and in Iceland they imitated courtly life at their homes as patrons of poets. A case in point is Sturla Sighvatsson. The story of Iceland in the thirteenth century is mainly told by the men of Sturlungar family, and their own political and cultural perspective governs their official version of events. These men were poets and writers, chieftains and lawspeakers, and friends of royalty in Norway. Is there another story to be told? Is there another audience lurking in the background? In this paper I intend to address this question through the poetic evidence of the sagas of Icelanders, analyzing two sagas which were written in the west of Iceland in the middle of thirteenth century. Laxdæla saga and Eyrbyggja saga reflect their authors’ different perspectives, while they have a lot in common. Which issues and concerns determine their differences? Let us take one example. Why is the author of Laxdæla disinterested in skaldic verse, and why does he even choose to quote skaldic stanzas? Similarly, how important are the poetic quotations to the author of Eyrbyggja? The answers may raise a number of issues concerning the narrative strategy of the sagas in general, as well as the cultural background of the authors.